2009
DOI: 10.3892/ijmm_00000147
|View full text |Cite
|
Sign up to set email alerts
|

Danazol regulates the functions of normal human endometrial stromal cell subpopulations by modifying endometrial cytokine networks

Abstract: Abstract. Local danazol therapy can improve endometriotic signs and symptoms without causing any menstrual disorders. As a consequence, certain direct actions of danazol on endometriotic tissues have been proposed, but the mechanisms of these actions have not been clarified. In the present study, the direct effects of danazol on normal human endometrial stromal cells (ESCs) were examined using in vitro decidualization assays. Danazol did not affect the viable cell numbers of unstimulated ESCs or 8Br-cAMP-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Danazol has been reported to decrease the production of inflammatory cytokines, including interleukin-6 and tumor necrosis factor-a, which may limit their ability to cause proliferation of CLL cells in vivo. 13 Danazol can also intercalate into cell membranes, 14 which may dysrupt growth-promoting signaling processes and account for a mechanism of action apparently independent of glucocorticoid, estrogen and androgen receptors (Figure 1d).…”
mentioning
confidence: 99%
“…Danazol has been reported to decrease the production of inflammatory cytokines, including interleukin-6 and tumor necrosis factor-a, which may limit their ability to cause proliferation of CLL cells in vivo. 13 Danazol can also intercalate into cell membranes, 14 which may dysrupt growth-promoting signaling processes and account for a mechanism of action apparently independent of glucocorticoid, estrogen and androgen receptors (Figure 1d).…”
mentioning
confidence: 99%
“…Tung et al [ 19 ] proposed that a reduction in blood CD23 level by danazol observed during endometriosis treatment suggested a direct effect on activated B cells in CLL [ 25 , 26 ]. Similarly, danazol can decrease production of inflammatory cytokines, such as interleukin-6 and tumor necrosis factor-alpha, which probably can restrict their ability to induce proliferation of CLL cells in vivo [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%